Managing an Atypical Case of Pediatric Cutaneous Polyarteritis Nodosa: Clinical Perspectives Managing Rare Presentation of Cutaneous Polyarteritis Nodosa in Pediatric Patient: Insight from a Case Study - Utama, Adelia Anggraini; Kisworini, Priyanti; Putri, Niarsari Anugrahing (Indonesian Journal of Case Reports, 2025)
Cutaneous polyarteritis nodosa is a rare form of necrotizing vasculitis affecting small and medium-sized arteries, characterized by localized inflammation and ischemia without systemic organ involvement. This case report highlights a 7-year-old girl who presented with severe cutaneous manifestations, including digital necrosis and livedo reticularis, accompanied by arthralgia and myalgia. Laboratory findings revealed elevated inflammatory markers and a high anti-streptolysin O titer, indicating a possible post-streptococcal etiology. Angiographic evidence confirmed arterial occlusion in the left hand. The patient was treated with high-dose intravenous methylprednisolone, anticoagulation, and long-term methotrexate, resulting in symptom resolution and sustained remission over one year. This case emphasized the importance of prompt recognition, diagnosis, and multidisciplinary management of cutaneous polyarteritis nodosa to prevent and improve outcomes.